Inducible nitric oxide synthase polymorphism is associated with the increased risk of differentiated gastric cancer in a Japanese population - Goto, Yasuyuki (Baishideng Publishing Group Co., Limited, 2006)
AIM: To examine the association of inducible nitric oxide synthase (iNOS) C150T polymorphism with gastric cancer, as well as with gastric atrophy and H pylori seropositivity. METHODS: A single nucleotide polymorphism of iNOS C150T was examined for 454 Japanese health checkup examinees (126 males and 328 females) aged 35 to 85 years without a history of cancer and 202 gastric cancer patients (134 males and 68 females) aged 33 to 94 years with pathologically confirmed diagnosis of gastric adenocarcinoma. RESULTS: The iNOS C150T polymorphism was not associated with gastric atrophy or with H pylori seropositivity. The odds ratio (OR) of the C/T + T/T for gastric cancer was increased without statistical significance (OR=1.19, 95% confidence interval (CI): 0.68-2.08). In the differentiated subgroup (n = 113), however, the OR of the C/T genotype for gastric cancer was significant (OR = 2.02, 95% CI: 1.04-3.92) relative to the C/C genotype. In addition, considering the location of gastric cancer (n = 105), there were significant differences between the controls and non-cardia group with the OR of 2.13 (95% CI: 1.08-4.18) for C/T and 1.94 (95% CI: 1.00-3.78) for C/T + T/T. CONCLUSION: The iNOS C150T polymorphism is associated with the risk of H pylori-related gastric cancer in a Japanese population. This polymorphism may play an important role in increasing the risk of gastric cancer in Asian countires with the highest rates of gastric cancer.